Additional file 3 of Location of studies and evidence of effects of herbivory on Arctic vegetation: a systematic map - E. M. Soininen (11566553); I. C. Barrio (11566556); R. Bjørkås (11566559); K. Björnsdóttir (11566562); D. Ehrich (11566565); K. A. Hopping (11566568); E. Kaarlejärvi (11566571); A. L. Kolstad (11566574); S. Abdulmanova (11566577); R. G. Björk (11566580); C. G. Bueno (11566583); I. Eischeid (11566586); et al. (2021)
Additional file 3. List of articles. Contains all search results retrieved from the literature searches with information on exclusion stage and (for full text stage) reasons for exclusion, and definitions of variables.